Cold Resources Empowering Warm Classrooms: Knowledge Construction and Educational Realization of Ice-Snow Study Tours from the Perspective of New Liberal Arts - Ying Guo (Education Research on Study Tours and Practice, 2026)
Guided by the important concept that "ice and snow are also gold and silver mountains," ice and snow resources have evolved from regional natural endowments into comprehensive development carriers with educational, cultural and economic values. The construction of New Liberal Arts, with interdisciplinary integration, practice orientation, digital transformation and value guidance as its core essentials, provides theoretical support and directional guidance for the innovative development of ice and snow study tours. Relying on ice and snow scenarios, ice and snow study tours deeply integrate natural sciences, humanities and social sciences, digital technologies and practical teaching, completing the transformation from resource utilization to knowledge creation and from single experience to diversified education. From the perspective of New Liberal Arts interdisciplinary integration, this paper systematically explains the logic of knowledge integration, knowledge innovation and knowledge communication in ice and snow study tours, constructs an education realization path under the guidance of "five-in-one education," and puts forward high-quality development strategies from five dimensions: discipline integration, curriculum innovation, digital empowerment, talent construction and standardization. It aims to turn the "cold resources" of ice and snow into "hot classrooms" for fostering morality and talents, and provide theoretical references and practical paths for the coordinated development of the ice and snow economy and education, as well as the cultivation of interdisciplinary talents.